PENERAPAN TIPE THE POWER OF TWO PADA PEMBELAJARAN AKTIF DISERTAI LEMBAR KERJA SISWA (LKS) TERHADAP HASIL BELAJAR BIOLOGISISWA KELAS X SEMESTER 2 SMAN 2 KOTO XI TARUSAN - Marlina, Leni; Armen, Armen; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACT The background of this research is the low yields of learning outcomes at Biology of SMA  N 2 Koto  XI Tarusan,  shown  by the average daily test  of students on the material ecosystem Biology and environmental pollution which are still under Complete Minimal Criteria   established the school. To overcome these problems, the teachers need to be creative using appropriate teaching strategies so that the learning can increase students motivation and interest. One of the strategies that requires involvement of the student is to implement an active learning strategy named The Power Of Two  and Student Worksheet. This study aimed to examine the effects The Power Of Two strategy to learning outcomes at Biology of Class X SMA N 2 Koto XI Tarusan Academic Year 2012/2013. When the study was conducted in May 2013, this type of research is experimental with a population  of  class  X  SMA  N  2  Koto  XI Tarusan  listed  in  the  school  year2012/2013 as many as 248 students and grouped into 8 classes, while the sample is X1 class as a class experiments  and class control X3 as the experimental class were taken by using purposive random sampling technique. The study design was a randomized Only Control Group Design. Based on the analysis results, obtained average achievement test on the experimental class was 70.25 and standard deviation  6.38,  while  the  average  achievement  test  class  control  standard deviation of 61.61 and 12.48 after testing with the t-test obtained t = 3.34 and t- table = 1.6705 means that t > t table, then the hypothesis in this study with 95 % confidence interval is received. It can be concluded that the use of The Power Of Two strategy with Student Worksheet has good effects on learning outcomes at Biology of class X SMAN 2 Koto XI Tarusan Academic Year 2012/2013.